THE IMPACT OF MANAGERIAL CONSULTATION ON VOICE FUTILITY AND INTENT TO QUIT WITH TRANSFORMATIONAL LEADERSHIPAS MODERATOR: A MEDIATING ROLE OF FELT OBLIGATION TOWARDS CONSTRUCTIVE CHANGE - G. Alyusef, Muna Ibrahim; Zhang, Peng Cheng (European Scientific Journal, ESJ, 2015)
Employee voice is essential to the constructive progress of any organization. While many organizations have adapted to the culture of more open communication, some are still lagging behind in providing employees with the power to speak up to their supervisors. The barrier has led to general job employees’ dissatisfaction frequently resulting in employee’s intent to quit. Managerial consultation is, hence, essential to avoid such situations while a more supportive leadership provides employees with the motivation and inspiration they require to feel obliged to bring about positive change in their organizations. This study has proposed four hypotheses based on managerial consultation, voice futility, and intent to quit while transformational leadership and feeling obliged towards constructive change have been used as the moderator and mediator, respectively. The study concludes that there exists positive relationship between managerial consultation, voice futility, and intent to quit, provided that effective managerial consultation reduces the intent to quit and vice versa.